1999
DOI: 10.2116/analsci.15.303
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Maxima on Conductometric Titration Curves of Sulfonic Acids and the Evidence of Strong Homoconjugation Reactions in Benzonitrile

Abstract: The conductometric titrations of acids with bases usually give decreasing or increasing straight lines from the beginning to the equivalence point in protic solvents. However, in aprotic solvents, such as acetone 1 and acetonitrile 2 , maxima at the half equivalence point on titration curves have been observed for carboxylic acids with amine bases. The cause of the maxima at the half equivalence point has been attributed to homoconjugation reactions 2 between an acid (HA) and the conjugate base anion (A -) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Some sulfonic acids, such as methanesulfonic and p-toluenesulfonic acids, have been observed to be weak acids in benzonitrile (DN = 11.9, AN = 15.5) to form the 1:2-type homoconjugated species by means of conductometry [20]. Meanwhile, conductometric titrations with Et 3 N of di-and trisulfonic acids in MeCN have revealed the strong homoconjugation for the di-and trisulfonic acids [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some sulfonic acids, such as methanesulfonic and p-toluenesulfonic acids, have been observed to be weak acids in benzonitrile (DN = 11.9, AN = 15.5) to form the 1:2-type homoconjugated species by means of conductometry [20]. Meanwhile, conductometric titrations with Et 3 N of di-and trisulfonic acids in MeCN have revealed the strong homoconjugation for the di-and trisulfonic acids [21].…”
Section: Introductionmentioning
confidence: 99%
“…In specific cases, careful experimentation has yielded unexpected insights. Conductometric titration of sulfonic acids in benzonitrile has demonstrated that the active species is trimeric in acid; carefully conducted IR spectroscopic studies revealed that triflic acid protonates water in nonpolar organic solvents to form a hydronium triflate ion pair, but the stronger acid bis­(trifluoromethyl)­sulfonyl imine (HNTf 2 ) instead forms a hydrogen-bonded complex without proton transfer . Nonetheless, most acid/solvent combinations that find use in organic chemistry remain incompletely characterized.…”
mentioning
confidence: 99%
“…8 Hojo and Chen investigated homoconjugation reactions in this solvent. 9 As can be seen from the literature data, nitriles are extensively used as a medium in potentiometric determinations of many acidic substances. A glass electrode is most frequently used as an indicator electrode, in both aqueous and non-aqueous media.…”
mentioning
confidence: 99%